PENGEMBANGAN BAHAN AJAR MENYIMAK UNTUK SISWA SEKOLAH KEJURUAN - Asmiati, Asmiati; Rachmawati, Rachmawati; Muhammad, Damris (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2012)
This study was aimed at developing listening material and teaching aid. The teaching aid makes use of computer. The purpose of using computer to help students in order to make the teaching-learning process effective and interesting. In constructing or developing the thesis, R & D method is applied. This method consists of 1) assessing to identify goal, 2) conducting instructional analysis, 3) analyzing learners and contexts, 4) writing performance objective, 5) developing assessment instruments, 6) developing instructional strategy, 7) developing and select instructional materials, 8) designing and conducting formative evaluation of instruction, 9) revising instruction, and 10) designing and conducting summative evaluation. The result of the developmental study shows that the teaching aid is good. It gets 3,75. The students who are involved in this study is the students of vocational high school grade X of tourism program. All of them enjoyed the lesson. It can be concluded that the listening material and teaching aid is effective and hence it is easy to be operated. Keyword: listening material, and teaching aid